Socially-supportive norms and mutual aid of people who use opioids: An analysis of Reddit during the initial COVID-19 pandemic. (1st May 2021) - Bunting, Amanda M.; Frank, David; Arshonsky, Joshua; Bragg, Marie A.; Friedman, Samuel R.; Krawczyk, Noa
Highlights: COVID-19 shifted the daily lives and social networks of persons who use opioids. Reddit was an important venue for social engagement during the pandemic. Persons who use opioids used Reddit to provide mutual aid and social support. Abstract: Background: Big events (i.e., unique historical disruptions) like the COVID-19 epidemic and its associated period of social distancing can transform social structures, social interactions, and social norms. Social distancing rules and the fear of infection have greatly reduced face-to-face interactions, increased loneliness, reduced ties to helping institutions, and may also have disrupted the opioid use behaviors of people who use drugs. This research used Reddit to examine the impact of COVID-19 on the social networks and social processes of people who use opioids. Methods: Data were collected from the social media forum, Reddit.com. At the beginning of the COVID-19 pandemic in the U.S. (March 5, 2020, to May 13, 2020), 2, 000 Reddit posts were collected from the two most popular opioid subreddits (r/OpiatesRecovery, r/Opiates). Posts were reviewed for relevance to COVID-19 and opioid use resulting in a final sample of 300. Thematic analysis was guided by the Big Events framework. Results: The COVID-19 pandemic was found to create changes in the social networks and daily lives among persons who use opioids. Adaptions to these changes shifted social networks leading to robust social support and mutual aid on Reddit, including sharing and seeking advice on facing withdrawal, dealing with isolation, managing cravings, and accessing recovery resources. Conclusions: Reddit provided an important source of social support and mutual aid for persons who use opioids. Findings indicate online social support networks are beneficial to persons who use opioids, particularly during big events where isolation from other social support resources may occur.